Evaulating The Durability of Response in New Biologics for Psoriasis (Canadian Dermatology Today, 2023)
Psoriasis (PsO) is a chronic inflammatory disease with a prevalence estimated at 1–3%. Biologic therapies have revolutionized the treatment of PsO, with subsequent generations of biologics showing ever‑increasing efficacy. There are currently 12 originator biologics approved in Canada. In addition, numerous biosimilars have been approved. Phase 3 trials have reported efficacy ranging from PASI 75 rates of 49% from some of the earliest biologics still available, such as etanercept, up to PASI 90 response rates of 85% for the most recent biologics such as bimekizumab. With the number needed to treat to obtain a PASI 90 response approaching one with bimekizumab, it is important to ask how durable the response will be in order to avoid having to switch biologics after an initial response. This article will review my process for evaluating the durability of response of a new agent.